2016
DOI: 10.1002/job.2123
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor role overload and frustration as antecedents of abusive supervision: The moderating role of supervisor personality

Abstract: Summary The current research explores supervisor‐level antecedents of abusive supervision in the workplace. Specifically, this study introduces affective events theory to the abusive supervision literature to suggest that supervisor role overload, a work‐related event, leads to supervisor frustration. As an intense negative emotional reaction, frustration, in turn, triggers supervisors to exhibit abusive behaviors in the workplace. Supervisor personality traits—namely, neuroticism, conscientiousness, and agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
205
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(216 citation statements)
references
References 86 publications
(147 reference statements)
11
205
0
Order By: Relevance
“…As we introduced the study, we emphasised the importance of integrity of the scientific process. The employment of this data collection is consistent with existing literature, which has successfully utilised this data collection approach to test theoretical models (e.g., Eissa & Lester, ; Greenbaum et al, ). The aforementioned procedures and steps were also designed following the suggestions of prior scholars (e.g., Judge, Scott, & Ilies, ; Wheeler, Shanine, Leon, & Whitman, ).…”
Section: Methodssupporting
confidence: 68%
“…As we introduced the study, we emphasised the importance of integrity of the scientific process. The employment of this data collection is consistent with existing literature, which has successfully utilised this data collection approach to test theoretical models (e.g., Eissa & Lester, ; Greenbaum et al, ). The aforementioned procedures and steps were also designed following the suggestions of prior scholars (e.g., Judge, Scott, & Ilies, ; Wheeler, Shanine, Leon, & Whitman, ).…”
Section: Methodssupporting
confidence: 68%
“…Given the hindrance role of this behavior in the sustainable development of organizations, an increasing number of scholars have sought to probe its antecedents in order to lessen its deleterious effects. Prior empirical evidence has identified that some work stressors (e.g., exceedingly difficult job goals, task difficulty, role overload) are the antecedents of abusive supervision behavior (Burton et al, 2012;Mawritz et al, 2014;Eissa and Lester, 2017). These studies agree that work stressors often positively relate to negative behavior.…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, COR provides the theoretical basis for understanding why and when challenge-hindrance stressors have a similar effect on abusive supervision behavior. The previous study has proposed that work stressors (i.e., role overload) are positively associated with abusive supervision through psychological resource depletion (Eissa and Lester, 2017). However, to date, there has been no empirical research on the mediating mechanism of specific resource depletion variables between work stressors and abusive supervision behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antecedents of destructive leadership initially received less attention than the potential outcomes, but this has changed dramatically over the past five years (Tepper et al, 2017;Zhang & Bednall, 2015). Possible antecedents range from micro-level to macro-level factors, such as supervisor personality traits (Eissa & Lester, 2017) and stress caused by climate conditions (Van de Vliert, Matthiesen, Gangsøy, Landro, & Einarsen, 2010) to antecedents in the military context like lack of sleep (Olsen, Pallesen, Torsheim, & Espevik, 2016). In a recent meta-analysis, Zhang and Bednall (2015) categorised antecedents into four main groups: supervisor-related, organization-related and subordinate-related antecedents, in addition to, demographic characteristics of supervisors and subordinates.…”
Section: Antecedents Outcomes and Prevalence Of Destructive Leadershipmentioning
confidence: 99%